Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Real‐time geographic settling of a hybrid zone between the invasive winter moth ( Operophtera brumata L.) and the native Bruce spanworm ( O. bruceata Hulst) - Jeremy C. Andersen; Nathan P. Havill; George H. Boettner; Jennifer L. Chandler; Adalgisa Caccone; Joseph S. Elkinton (Molecular Ecology, 2022)
Hybridization plays an important and underappreciated role in shaping the evolutionary trajectories of species. Following the introduction of a non‐native organism to a novel habitat, hybridization with a native congener may affect the probability of establishment of the introduced species. In most documented cases of hybridization between a native and a non‐native species, a mosaic hybrid zone is formed, with hybridization occurring heterogeneously across the landscape. In contrast, most naturally occurring hybrid zones are clinal in structure. Here, we report on a long‐term microsatellite data set that monitored hybridization between the invasive winter moth, Operophtera brumata (Lepidoptera: Geometridae), and the native Bruce spanworm, O . bruceata , over a 12‐year period. Our results document one of the first examples of the real‐time formation and geographic settling of a clinal hybrid zone. In addition, by comparing one transect in Massachusetts where extreme winter cold temperatures have been hypothesized to restrict the distribution of winter moth, and one in coastal Connecticut, where winter temperatures are moderated by Long Island Sound, we found that the location of the hybrid zone appeared to be independent of environmental variables and maintained under a tension model wherein the stability of the hybrid zone was constrained by population density, reduced hybrid fitness, and low dispersal rates. Documenting the formation of a contemporary clinal hybrid zone may provide important insights into the factors that shaped other well‐established hybrid zones.

Demographic history and patterns of molecular evolution from whole genome sequencing in the radiation of Galapagos giant tortoises - Evelyn L. Jensen; Stephen J. Gaughran; Ryan C. Garrick; Michael A. Russello; Adalgisa Caccone (Molecular Ecology, 2021)
Whole genome sequencing provides deep insights into the evolutionary history of a species, including patterns of diversity, signals of selection, and historical demography. When applied to closely related taxa with a wealth of background knowledge, population genomics provides a comparative context for interpreting population genetic summary statistics and comparing empirical results with the expectations of population genetic theory. The Galapagos giant tortoises ( Chelonoidis spp.), an iconic rapid and recent radiation, offer such an opportunity. Here, we sequenced whole genomes from three individuals of the 12 extant lineages of Galapagos giant tortoise and estimate diversity measures and reconstruct changes in coalescent rate over time. We also compare the number of derived alleles in each lineage to infer how synonymous and nonsynonymous mutation accumulation rates correlate with population size and life history traits. Remarkably, we find that patterns of molecular evolution are similar within individuals of the same lineage, but can differ significantly among lineages, reinforcing the evolutionary distinctiveness of the Galapagos giant tortoise species. Notably, differences in mutation accumulation among lineages do not align with simple population genetic predictions, suggesting that the drivers of purifying selection are more complex than is currently appreciated. By integrating results from earlier population genetic and phylogeographic studies with new findings from the analysis of whole genomes, we provide the most in‐depth insights to date on the evolution of Galapagos giant tortoises, and identify discrepancies between expectation from population genetic theory and empirical data that warrant further scrutiny.

Four times out of Europe: Serial invasions of the winter moth, Operophtera brumata , to North America - Jeremy C. Andersen; Nathan P. Havill; Adalgisa Caccone; Joseph S. Elkinton (Molecular Ecology, 2021)
Reconstructing the geographic origins of non‐native species is important for studying the factors that influence invasion success, however; these analyses can be constrained by the amount of diversity present in the native and invaded regions, and by changes in the genetic background of the invading population following bottlenecks and/or hybridization events. Here we explore the geographical origins of the invasive winter moth ( Operopthera brumata L.) that has caused widespread defoliation to forests, orchards, and crops in Nova Scotia, British Columbia, Oregon, and the northeastern United States. It is not known whether these represent independent introductions to North America, or a “stepping stone” spread among regions. Using a combination of Bayesian assignment and approximate Bayesian computation methods, we analysed a population genetic data set of 24 microsatellite loci. We estimate that winter moth was introduced to North America on at least four occasions, with the Nova Scotian and British Columbian populations probably being introduced from France and Sweden, respectively; the Oregonian population probably being introduced from either the British Isles or northern Fennoscandia; and the population in the northeastern United States probably being introduced from somewhere in Central Europe. We discuss the impact of genetic bottlenecks on analyses meant to determine region of origin.

Genetically informed captive breeding of hybrids of an extinct species of Galapagos tortoise - Maud C. Quinzin; Jonathan Sandoval‐Castillo; Joshua M. Miller; Luciano B. Beheregaray; Michael A. Russello; Elizabeth A. Hunter; James P. Gibbs; Washington Tapia; Freddy Villalva; Adalgisa Caccone (Conservation Biology, 2019)
Hybridization poses a major challenge for species conservation because it threatens both genetic integrity and adaptive potential. Yet, hybridization can occasionally offer unprecedented opportunity for species recovery if the genome of an extinct taxon is present among living hybrids such that selective breeding could recapture it. We explored the design elements for establishing a captive‐breeding program for Galapagos tortoises ( Chelonoidis spp.) built around individuals with admixed ancestry involving an extinct species. The target individuals were hybrids between the extinct species from Floreana Island, C. niger , and an extant species, C. becki , which were recently found in the endemic range of C. becki , from Wolf Volcano on Isabela Island. We combined genotypic data from 35 tortoises with high ancestry from C. niger with forward‐in‐time simulations to explore captive breeding strategies that maximized overall genetic diversity and ancestry from C. niger while accommodating resource constraints, species biology, and the urgency to return tortoises to Floreana Island for facilitating ecosystem restoration. Overall genetic diversity was maximized when in the simulation tortoises were organized in relatively small breeding groups. Substantial amounts of the C. niger genome were captured despite limited resources available for selectively breeding tortoises in captivity. Genetic diversity was maximized when captive‐bred offspring were released to the wild rather than being used as additional breeders. Our results provide genetic‐based and practical guidance on the inclusion of hybrids with genomic representation from extinct taxa into species restoration programs and informs the ongoing debate on the value of hybrids in biodiversity conservation.

Widespread hybridization among native and invasive species of Operophtera moths (Lepidoptera: Geometridae) in Europe and North America - Jeremy C. Andersen; Nathan P. Havill; Hannah J. Broadley; George H. Boettner; Adalgisa Caccone; Joseph S. Elkinton (Biological Invasions, 2019)

The population genomics of multiple tsetse fly ( Glossina fuscipes fuscipes ) admixture zones in Uganda - Norah P. Saarman; Robert Opiro; Chaz Hyseni; Richard Echodu; Elizabeth A. Opiyo; Kirstin Dion; Thomas Johnson; Serap Aksoy; Adalgisa Caccone (Molecular Ecology, 2019)
Understanding the mechanisms that enforce, maintain or reverse the process of speciation is an important challenge in evolutionary biology. This study investigates the patterns of divergence and discusses the processes that form and maintain divergent lineages of the tsetse fly Glossina fuscipes fuscipes in Uganda. We sampled 251 flies from 18 sites spanning known genetic lineages and the four admixture zones between them. We apply population genomics, hybrid zone and approximate Bayesian computation to the analysis of three types of genetic markers: 55,267 double‐digest restriction site‐associated DNA (ddRAD) SNPs to assess genome‐wide admixture, 16 microsatellites to provide continuity with published data and accurate biogeographic modelling, and a 491‐bp fragment of mitochondrial cytochrome oxidase I and II to infer maternal inheritance patterns. Admixture zones correspond with regions impacted by the reorganization of Uganda's river networks that occurred during the formation of the West African Rift system over the last several hundred thousand years. Because tsetse fly population distributions are defined by rivers, admixture zones likely represent both old and new regions of secondary contact. Our results indicate that older hybrid zones contain mostly parental types, while younger zones contain variable hybrid types resulting from multiple generations of interbreeding. These findings suggest that reproductive barriers are nearly complete in the older admixture zones, while nearly absent in the younger admixture zones. Findings are consistent with predictions of hybrid zone theory: Populations in zones of secondary contact transition rapidly from early to late stages of speciation or collapse all together.

Ecological and evolutionary influences on body size and shape in the Galápagos marine iguana (Amblyrhynchus cristatus) - Ylenia Chiari; Scott Glaberman; Pedro Tarroso; Adalgisa Caccone; Julien Claude (Oecologia, 2016)

Ancient and modern colonization of North America by hemlock woolly adelgid, Adelges tsugae (Hemiptera: Adelgidae), an invasive insect from East Asia - Nathan P. Havill; Shigehiko Shiyake; Ashley Lamb Galloway; Robert G. Foottit; Guoyue Yu; Annie Paradis; Joseph Elkinton; Michael E. Montgomery; Masakazu Sano; Adalgisa Caccone (Molecular Ecology, 2016)
Hemlock woolly adelgid, Adelges tsugae , is an invasive pest of hemlock trees ( Tsuga ) in eastern North America. We used 14 microsatellites and mitochondrial COI sequences to assess its worldwide genetic structure and reconstruct its colonization history. The resulting information about its life cycle, biogeography and host specialization could help predict invasion by insect herbivores. We identified eight endemic lineages of hemlock adelgids in central China, western China, Ulleung Island (South Korea), western North America, and two each in Taiwan and Japan, with the Japanese lineages specializing on different Tsuga species. Adelgid life cycles varied at local and continental scales with different sexual, obligately asexual and facultatively asexual lineages. Adelgids in western North America exhibited very high microsatellite heterozygosity, which suggests ancient asexuality. The earliest lineages diverged in Asia during Pleistocene glacial periods, as estimated using approximate Bayesian computation. Colonization of western North America was estimated to have occurred prior to the last glacial period by adelgids directly ancestral to those in southern Japan, perhaps carried by birds. The modern invasion from southern Japan to eastern North America caused an extreme genetic bottleneck with just two closely related clones detected throughout the introduced range. Both colonization events to North America involved host shifts to unrelated hemlock species. These results suggest that genetic diversity, host specialization and host phylogeny are not predictive of adelgid invasion. Monitoring non‐native sentinel host trees and focusing on invasion pathways might be more effective methods of preventing invasion than making predictions using species traits or evolutionary history.

Genetics of a head-start program to guide conservation of an endangered Galápagos tortoise (Chelonoidis ephippium) - Evelyn L. Jensen; Washington Tapia; Adalgisa Caccone; Michael A. Russello (Conservation Genetics, 2015)

Lineage fusion in G alápagos giant tortoises - Ryan C. Garrick; Edgar Benavides; Michael A. Russello; Chaz Hyseni; Danielle L. Edwards; James P. Gibbs; Washington Tapia; Claudio Ciofi; Adalgisa Caccone (Molecular Ecology, 2014)
Although many classic radiations on islands are thought to be the result of repeated lineage splitting, the role of past fusion is rarely known because during these events, purebreds are rapidly replaced by a swarm of admixed individuals. Here, we capture lineage fusion in action in a Galápagos giant tortoise species, Chelonoidis becki , from Wolf Volcano (Isabela Island). The long generation time of Galápagos tortoises and dense sampling (841 individuals) of genetic and demographic data were integral in detecting and characterizing this phenomenon. In C. becki, we identified two genetically distinct, morphologically cryptic lineages. Historical reconstructions show that they colonized Wolf Volcano from Santiago Island in two temporally separated events, the first estimated to have occurred ~199 000 years ago. Following arrival of the second wave of colonists, both lineages coexisted for approximately ~53 000 years. Within that time, they began fusing back together, as microsatellite data reveal widespread introgressive hybridization. Interestingly, greater mate selectivity seems to be exhibited by purebred females of one of the lineages. Forward‐in‐time simulations predict rapid extinction of the early arriving lineage. This study provides a rare example of reticulate evolution in action and underscores the power of population genetics for understanding the past, present and future consequences of evolutionary phenomena associated with lineage fusion.

Habitat fragmentation and the genetic structure of the Amazonian palm Mauritia flexuosa L.f. (Arecaceae) on the island of Trinidad - Sarah Federman; Chaz Hyseni; Wendy Clement; Michael P. Oatham; Adalgisa Caccone (Conservation Genetics, 2014)

Urban population genetics of slum‐dwelling rats ( R attus norvegicus ) in S alvador, B razil - Brittney Kajdacsi; Federico Costa; Chaz Hyseni; Fleur Porter; Julia Brown; Gorete Rodrigues; Helena Farias; Mitermayer G. Reis; James E. Childs; Albert I. Ko; Adalgisa Caccone (Molecular Ecology, 2013)
Throughout the developing world, urban centres with sprawling slum settlements are rapidly expanding and invading previously forested ecosystems. Slum communities are characterized by untended refuse, open sewers and overgrown vegetation, which promote rodent infestation. N orway rats ( R attus norvegicus ) are reservoirs for epidemic transmission of many zoonotic pathogens of public health importance. Understanding the population ecology of R . norvegicus is essential to formulate effective rodent control strategies, as this knowledge aids estimation of the temporal stability and spatial connectivity of populations. We screened for genetic variation, characterized the population genetic structure and evaluated the extent and patterns of gene flow in the urban landscape using 17 microsatellite loci in 146 rats from nine sites in the city of S alvador, B razil. These sites were divided between three neighbourhoods within the city spaced an average of 2.7 km apart. Surprisingly, we detected very little relatedness among animals trapped at the same site and found high levels of genetic diversity, as well as structuring across small geographical distances. Most F ST comparisons among sites were statistically significant, including sites R . norvegicus in S alvador, linked to the heterogeneous urban landscape. Future rodent control measures need to take into account the spatial and temporal linkage of rat populations in S alvador, as revealed by genetic data, to develop informed eradication strategies.

Genetic isolation within the malaria mosquito Anopheles melas - Kevin C. Deitz; Giri Athrey; Michael R. Reddy; Hans J. Overgaard; Abrahan Matias; Musa Jawara; Alessandra Della Torre; Vincenzo Petrarca; João Pinto; Anthony E. Kiszewski; Pierre Kengne; Carlo Costantini; et al. (Molecular Ecology, 2013)

Genetic isolation within the malaria mosquito A nopheles melas - Kevin C. Deitz; Giri Athrey; Michael R. Reddy; Hans J. Overgaard; Abrahan Matias; Musa Jawara; Alessandra della Torre; Vincenzo Petrarca; João Pinto; Anthony E. Kiszewski; Pierre Kengne; Carlo Costantini; et al. (Molecular Ecology, 2012)
Anopheles melas is a brackish water–breeding member of the Anopheles gambiae complex that is distributed along the coast of West Africa and is a major malaria vector within its range. Because little is known about the population structure of this species, we analysed 15 microsatellite markers and 1161 bp of mt DNA in 11 A. melas populations collected throughout its range. Compared with its sibling species A. gambiae , A. melas populations have a high level of genetic differentiation between them, representing its patchy distribution due to its fragmented larval habitat that is associated with mangroves and salt marsh grass. Populations clustered into three distinct groups representing Western Africa, Southern Africa and Bioko Island populations that appear to be mostly isolated. Fixed differences in the mt DNA are present between all three clusters, and a Bayesian clustering analysis of the microsatellite data found no evidence for migration from mainland to Bioko Island populations, and little migration was evident between the Southern to the Western cluster. Surprisingly, mt DNA divergence between the three A. melas clusters is on par with levels of divergence between other species of the A. gambiae complex, and no support for monophyly was observed in a maximum‐likelihood phylogenetic analysis. Finally, an approximate Bayesian analysis of microsatellite data indicates that Bioko Island A. melas populations were connected to the mainland populations in the past, but became isolated, presumably when sea levels rose after the last glaciation period (≥10 000–11 000 bp ). This study has exposed species‐level genetic divergence within A. melas and also has implications for control of this malaria vector.

Isolation of 13 novel highly polymorphic microsatellite loci for the Amazonian Palm Mauritia flexuosa L.f. (Arecaceae) - Sarah Federman; Chaz Hyseni; Wendy Clement; Adalgisa Caccone (Conservation Genetics Resources, 2012)

Unravelling the peculiarities of island life: vicariance, dispersal and the diversification of the extinct and extant giant Galápagos tortoises - NIKOS POULAKAKIS; MICHAEL RUSSELLO; DENNIS GEIST; ADALGISA CACCONE (Molecular Ecology, 2012)
In isolated oceanic islands, colonization patterns are often interpreted as resulting from dispersal rather than vicariant events. Such inferences may not be appropriate when island associations change over time and new islands do not form in a simple linear trend. Further complexity in the phylogeography of ocean islands arises when dealing with endangered taxa as extinctions, uncertainty on the number of evolutionary ‘units’, and human activities can obscure the progression of colonization events. Here, we address these issues through a reconstruction of the evolutionary history of giant Galápagos tortoises, integrating DNA data from extinct and extant species with information on recent human activities and newly available geological data. Our results show that only three of the five extinct or nearly extinct species should be considered independent evolutionary units. Dispersal from mainland South America started at approximately 3.2 Ma after the emergence of the two oldest islands of San Cristobal and Española. Dispersal from older to younger islands began approximately 1.74 Ma and was followed by multiple colonizations from different sources within the archipelago. Vicariant events, spurred by island formation, coalescence, and separation, contributed to lineage diversifications on Pinzón and Floreana dating from 1.26 and 0.85 Ma. This work provides an example of how to reconstruct the history of endangered taxa in spite of extinctions and human‐mediated dispersal events and highlights the need to take into account both vicariance and dispersal when dealing with organisms from islands whose associations are not simply explained by a linear emergence model.

Species-specific evolution of class I MHC genes in iguanas (Order: Squamata; Subfamily: Iguaninae) - Scott Glaberman; Adalgisa Caccone (Immunogenetics, 2008)

Independent evolutionary origins of landlocked alewife populations and rapid parallel evolution of phenotypic traits - ERIC P. PALKOVACS; KIRSTIN B. DION; DAVID M. POST; ADALGISA CACCONE (Molecular Ecology, 2008)
Alewife, Alosa pseudoharengus , populations occur in two discrete life‐history variants, an anadromous form and a landlocked (freshwater resident) form. Landlocked populations display a consistent pattern of life‐history divergence from anadromous populations, including earlier age at maturity, smaller adult body size, and reduced fecundity. In Connecticut (USA), dams constructed on coastal streams separate anadromous spawning runs from lake‐resident landlocked populations. Here, we used sequence data from the mtDNA control region and allele frequency data from five microsatellite loci to ask whether coastal Connecticut landlocked alewife populations are independently evolved from anadromous populations or whether they share a common freshwater ancestor. We then used microsatellite data to estimate the timing of the divergence between anadromous and landlocked populations. Finally, we examined anadromous and landlocked populations for divergence in foraging morphology and used divergence time estimates to calculate the rate of evolution for foraging traits. Our results indicate that landlocked populations have evolved multiple times independently. Tests of population divergence and estimates of gene flow show that landlocked populations are genetically isolated, whereas anadromous populations exchange genes. These results support a ‘phylogenetic raceme’ model of landlocked alewife divergence, with anadromous populations forming an ancestral core from which landlocked populations independently diverged. Divergence time estimates suggest that landlocked populations diverged from a common anadromous ancestor no longer than 5000 years ago and perhaps as recently as 300 years ago, depending on the microsatellite mutation rate assumed. Examination of foraging traits reveals landlocked populations to have significantly narrower gapes and smaller gill raker spacings than anadromous populations, suggesting that they are adapted to foraging on smaller prey items. Estimates of evolutionary rates (in haldanes) indicate rapid evolution of foraging traits, possibly in response to changes in available resources.

Patterns of association between Symbiodinium and members of the Montastraea annularis species complex on spatial scales ranging from within colonies to between geographic regions - Melissa Garren; Sheila M. Walsh; Adalgisa Caccone; Nancy Knowlton (Coral Reefs, 2006)

Development of new microsatellite loci and evaluation of loci from other pinniped species for the Galápagos sea lion (Zalophus californianus wollebaeki) - Jochen B.W. Wolf; Diethard Tautz; Adalgisa Caccone; Sebastian Steinfartz (Conservation Genetics, 2006)

Genetic evaluation of a proposed introduction: the case of the greater prairie chicken and the extinct heath hen - Eric P. Palkovacs; Adam J. Oppenheimer; Eugene Gladyshev; John E. Toepfer; George Amato; Thomas Chase; Adalgisa Caccone (Molecular Ecology, 2004)
Population introduction is an important tool for ecosystem restoration. However, before introductions should be conducted, it is important to evaluate the genetic, phenotypic and ecological suitability of possible replacement populations. Careful genetic analysis is particularly important if it is suspected that the extirpated population was unique or genetically divergent. On the island of Martha's Vineyard, Massachusetts, the introduction of greater prairie chickens ( Tympanuchus cupido pinnatus ) to replace the extinct heath hen ( T. cupido cupido ) is being considered as part of an ecosystem restoration project. Martha's Vineyard was home to the last remaining heath hen population until its extinction in 1932. We conducted this study to aid in determining the suitability of greater prairie chickens as a possible replacement for the heath hen. We examined mitochondrial control region sequences from extant populations of all prairie grouse species ( Tympanuchus ) and from museum skin heath hen specimens. Our data suggest that the Martha's Vineyard heath hen population represents a divergent mitochondrial lineage. This result is attributable either to a long period of geographical isolation from other prairie grouse populations or to a population bottleneck resulting from human disturbance. The mtDNA diagnosability of the heath hen contrasts with the network of mtDNA haplotypes of other prairie grouse ( T. cupido attwateri, T. pallidicinctus and T. phasianellus ), which do not form distinguishable mtDNA groupings. Our findings suggest that the Martha's Vineyard heath hen was more genetically isolated than are current populations of prairie grouse and place the emphasis for future research on examining prairie grouse adaptations to different habitat types to assess ecological exchangeability between heath hens and greater prairie chickens.

Potential genetic consequences of a recent bottleneck in the Amur tiger of - Michael A. Russello; Eugene Gladyshev; Dale Miquelle; Adalgisa Caccone (Conservation Genetics, 2004)

Genetic structure of Mesoamerican populations of Big‐leaf mahogany ( Swietenia macrophylla ) inferred from microsatellite analysis - Rachel Roth Novick; Christopher w. Dick; Maristerra R. Lemes; Carlos Navarro; Adalgisa Caccone; Eldredge Bermingham (Molecular Ecology, 2003)
While microsatellites have been used to examine genetic structure in local populations of Neotropical trees, genetic studies based on such high‐resolution markers have not been carried out for Mesoamerica as a whole. Here we assess the genetic structure of the Mesoamerican mahogany Swietenia macrophylla King (big‐leaf mahogany), a Neotropical tree species recently listed as endangered in CITES which is commercially extinct through much of its native range. We used seven variable microsatellite loci to assess genetic diversity and population structure in eight naturally established mahogany populations from six Mesoamerican countries. Measures of genetic differentiation ( F ST and R ST ) indicated significant differences between most populations. Unrooted dendrograms based on genetic distances between populations provide evidence of strong phylogeographic structure in Mesoamerican mahogany. The two populations on the Pacific coasts of Costa Rica and Panama were genetically distant from all the others, and from one another. The remaining populations formed two clusters, one comprised of the northern populations of Mexico, Belize and Guatemala and the other containing the southern Atlantic populations of Nicaragua and Costa Rica. Significant correlation was found between geographical distance and all pairwise measures of genetic divergence, suggesting the importance of regional biogeography and isolation by distance in Mesoamerican mahogany. The results of this study demonstrate greater phylogeographic structure than has been found across Amazon basin S. macrophylla . Our findings suggest a relatively complex Mesoamerican biogeographic history and lead to the prediction that other Central American trees will show similar patterns of regional differentiation.

Analysis of a Shift in Codon Usage in Drosophila - Jeffrey R. Powell; Erminia Sezzi; Etsuko N. Moriyama; Jennifer M. Gleason; Adalgisa Caccone (Journal of Molecular Evolution, 2003)

Are the native giant tortoises from the Seychelles really extinct? A genetic perspective based on mtDNA and microsatellite data - Eric P. Palkovacs; Monique Marschner; Claudio Ciofi; Justin Gerlach; Adalgisa Caccone (Molecular Ecology, 2003)
The extinction of the giant tortoises of the Seychelles Archipelago has long been suspected but is not beyond doubt. A recent morphological study of the giant tortoises of the western Indian Ocean concluded that specimens of two native Seychelles species survive in captivity today alongside giant tortoises of Aldabra, which are numerous in zoos as well as in the wild. This claim has been controversial because some of the morphological characters used to identify these species, several measures of carapace morphology, are reputed to be quite sensitive to captive conditions. Nonetheless, the potential survival of giant tortoise species previously thought extinct presents an exciting scenario for conservation. We used mitochondrial DNA sequences and nuclear microsatellites to examine the validity of the rediscovered species of Seychelles giant tortoises. Our results indicate that the morphotypes suspected to represent Seychelles species do not show levels of variation and genetic structuring consistent with long periods of reproductive isolation. We found no variation in the mitochondrial control region among 55 individuals examined and no genetic structuring in eight microsatellite loci, pointing to the survival of just a single lineage of Indian Ocean tortoises.

Genetic divergence, phylogeography and conservation units of giant tortoises from Santa Cruz and Pinzón, Galápagos Islands - Luciano B. Beheregaray; Claudio Ciofi; Adalgisa Caccone; James P. Gibbs; Jeffrey R. Powell (Conservation Genetics, 2003)

Microsatellite analysis of genetic divergence among populations of giant Galápagos tortoises - Claudio Ciofi; Michel C. Milinkovitch; James P. Gibbs; Adalgisa Caccone; Jeffrey R. Powell (Molecular Ecology, 2002)
Giant Galápagos tortoises represent an interesting model for the study of patterns of genetic divergence and adaptive differentiation related to island colonization events. Recent mitochondrial DNA work elucidated the evolutionary history of the species and helped to clarify aspects of nomenclature. We used 10 microsatellite loci to assess levels of genetic divergence among and within island populations. In particular, we described the genetic structure of tortoises on the island of Isabela, where discrimination of different taxa is still subject of debate. Individual island populations were all genetically distinct. The island of Santa Cruz harboured two distinct populations. On Isabela, populations of Volcan Wolf, Darwin and Alcedo were significantly different from each other. On the other hand, Volcan Wolf showed allelic similarity with the island of Santiago. On Southern Isabela, lower genetic divergence was found between Northeast Sierra Negra and Volcan Alcedo, while patterns of gene flow were recorded among tortoises of Cerro Azul and Southeast Sierra Negra. These tortoises have endured heavy exploitation during the last three centuries and recently attracted much concern due to the current number of stochastic and deterministic threats to extant populations. Our study complements previous investigation based on mtDNA diversity and provides further information that may help devising tortoise management plans.